Between Traditions and Innovations: Culinary Boutique Tourism in the Hinterland of Mediterranean Tourist Destinations - Topole, Maja; Pipan, Primož (Traditiones, 2020)
The article presents two good practices in culinary boutique tourism from the Slovenian Mediterranean hinterland. The authors believe that they stand out in terms of content, innovation, organization, and personalized approach. The two tourist farms covered are very successful in networking and cooperation with other local producers and food suppliers. They have received a lot of media attention due to their activities and character. They have also received significant recognition at the national level. They educate visitors in search of unique culinary experiences, in their view, promote the cultural heritage, and increase the visibility of their region. As the authors note, culinary heritage, combined with innovation, is a vital element for the survival of small farms. Prispevek predstavlja dobri praksi s področja butičnega kulinaričnega turizma iz slovenskih zalednih sredozemskih turističnih destinacij. Po mnenju avtorjev praksi izstopata po vsebini, inovativnosti, organizaciji in personaliziranem pristopu. Obravnavani turistični kmetiji, ki ju odlikujeta mreženje in sodelovanje z drugimi lokalnimi pridelovalci in ponudniki hrane, sta bili zaradi svojega dela deležni zanimanja medijev, prejeli pa sta tudi visoka priznanja na državni ravni. Kmetiji izobražujeta obiskovalce, ki iščejo kulinarična doživetja in izkušnje in, kot sami pravijo, skrbita za promocijo kulturne dediščine in prepoznavnost regije. Avtorja ugotavljata, da je prehranska dediščina v kombinaciji z inovacijami ključna prvina za preživetje malih kmetij.